A Culpa e suas relações com a religiosidade e com o sentido da vida - Pereira, Gylmara de Araújo (2012)
This study started from the assumption that religiosity is associated with culpability, since, for some religions, the emphasis on sin and on purification rites is part of its salvific cosmovision. This way, the goal of this study is to know the relations between the dimensions of guilt (subjective, objective and temporal), religious attitudes and the meaning of life. 213 academic students (of Science of Religions, Pedagogy and Accounting) took part in the research. Despite of, the majority of respondents was of the Protestant religion (33,8%) and female (70,4%). The age average was 28,5 (SD=9,9), ranging from 18 to 63 years old. The data were collected through the following instruments: Religious Attitude Scale, Meaning of Life Questionnaire, Guilt Multidimensional Scale, Ontological Time Perception Scale and a socialdemographic questionnaire. The results suggest that both the religious feeling and the search for meaning are directly associated with the three dimensions of guilt. The religious corporeity, however, is positively correlated with subjective and objective guilts. In turn, the religious behavior is correlated with subjective guilt. The results also indicate that the presence of meaning is inversely related to temporal guilt, and the item there is a long distance between who I am and who I could be is associated with both subjective and temporal guilts. Such findings are discussed in light of Viktor Frankl s existential analysis. It was concluded that, if on the one hand more religious people are more susceptible to culpability, on the other hand guilt also comes from the ontological perspective, when human being fails to peform his duty-being.